2011
DOI: 10.1159/000333793
|View full text |Cite
|
Sign up to set email alerts
|

Novel Anti-Inflammatory Effects of Repaglinide in Rodent Models of Inflammation

Abstract: Background: Repaglinide is an FDA-approved treatment for type 2 diabetes mellitus. The anti-inflammatory effect of repaglinide in the absence of diabetes has not been reported previously. It is the objective of this set of studies to investigate the potential anti-inflammatory effects of repaglinide. Method: The in vivo anti-inflammatory effects of repaglinide were studied in two different models of delay type hyperreactivity (DTH) response induced by sheep red blood cells (sRBC) and 2,5′-dinitrofluorobenzene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 83 publications
(49 reference statements)
0
4
0
Order By: Relevance
“…Repaglinide efficaciously downregulated the resulting ear swelling response with sheep red blood cells and decreased serum TNF-α level and bronchial alveolar lavage fluid MCP-1 levels in LPS-challenged animals. 67 In addition, change of treatment from glimepiride to repaglinide in Japanese patients with T2DM reduced the levels of plasminogen activator inhibitor-1, hsCRP, and urinary 8-hydroxydeoxyguanosine. 68 Similarly, a study by Assaloni et al showed that controlling postprandial hyperglycemia with meglitinide significantly improves the cluster of oxidative stress (reduces nitrotyrosine, malondialdehyde, and oxidized low-density lipoprotein levels) and inflammation markers (decreases IL-6, IL-18, and TNF-α) that are increased in the postprandial state in patients with diabetes.…”
Section: Anti-inflammatory Effect Of Oral Hypoglycemic Agentsmentioning
confidence: 97%
See 1 more Smart Citation
“…Repaglinide efficaciously downregulated the resulting ear swelling response with sheep red blood cells and decreased serum TNF-α level and bronchial alveolar lavage fluid MCP-1 levels in LPS-challenged animals. 67 In addition, change of treatment from glimepiride to repaglinide in Japanese patients with T2DM reduced the levels of plasminogen activator inhibitor-1, hsCRP, and urinary 8-hydroxydeoxyguanosine. 68 Similarly, a study by Assaloni et al showed that controlling postprandial hyperglycemia with meglitinide significantly improves the cluster of oxidative stress (reduces nitrotyrosine, malondialdehyde, and oxidized low-density lipoprotein levels) and inflammation markers (decreases IL-6, IL-18, and TNF-α) that are increased in the postprandial state in patients with diabetes.…”
Section: Anti-inflammatory Effect Of Oral Hypoglycemic Agentsmentioning
confidence: 97%
“…Although novel anti-inflammatory effects of repaglinide in nondiabetic animals were established, the high doses required for an efficacious effect would make this application impractical in the clinic. 67 Repaglinide was studied in two different models of delay-type hyperreactivity response induced by sheep red blood cells and 2,5′-dinitrofluorobenzene, and in two different rodent models of LPS challenge. Repaglinide efficaciously downregulated the resulting ear swelling response with sheep red blood cells and decreased serum TNF-α level and bronchial alveolar lavage fluid MCP-1 levels in LPS-challenged animals.…”
Section: Anti-inflammatory Effect Of Oral Hypoglycemic Agentsmentioning
confidence: 99%
“…It is noteworthy that Kir6 inhibitors tested here are used as short acting insulin secretagogues that have also been shown to reduce systemic inflammation [22,42] and Assloni et al [43] showed that controlling post-prandial hyperglycemia by mitiglinide improves cluster of oxidative and inflammatory markers in diabetic patients. However, it remains unclear whether these effects are direct or reduction in inflammation is an indirect consequence of reduced glucose levels [44].…”
Section: Discussionmentioning
confidence: 91%
“…[ 19 20 ] Newer sulfonylurea drugs such as gliclazide and glimepiride are more efficient in reducing inflammatory markers compared to other drugs of this group. [ 21 22 23 ] Some studies have demonstrated that acarbose can reduce blood pressure, lipid, body weight, inflammatory markers, and cardiovascular adverse events. [ 12 13 14 ] A study of these effects concluded that in diabetic patients who received acarbose, insulin resistance index, interleukin 6 (IL-6), and interleukin 1β (IL-1β) showed no significant reduction after 3 months of treatment.…”
Section: Discussionmentioning
confidence: 99%